Effect of Prophylactic Central Lymph Node Dissection on Locoregional Recurrence in Patients with Papillary Thyroid Microcarcinoma. (15th November 2021) - Yang, Peipei; Li, Jianming; Jing, Haoyu; Chen, Qiyang; Song, Xinxin; Qian, Linxue
Abstract : There is a consensus that central compartment lymph node dissection or modified radical lateral neck dissection should be performed in papillary thyroid microcarcinoma (PTMC) patients with lymph node metastases. Prophylactic central lymph node dissection (PCLND) in patients with clinically node-negative (cN0) PTMC to reduce locoregional recurrence (LRR) rate and improve prognosis remains controversial. The present study aimed to analyze the effect of PCLND on LRR and postoperative complications of PTMC in cN0 patients. We reviewed a cohort of patients with cN0 PTMC who underwent surgery between January 1997 and October 2019. The patients were divided into the PCLND and no lymph node dissection (NLND) groups. Kaplan–Meier curves were constructed to estimate 15-year locoregional recurrence-free survival rate of the two groups, and the difference was compared by the log-rank test. Three Cox regression models were performed to evaluate the correlation between PCLND and LRR. All patients underwent thyroidectomy, and 25 patients developed LRR; of whom, 23 underwent PCLND at initial surgery and 2 went without lymph node dissection. Cox regression analysis showed that PCLND had no effect on LRR. Postoperative hematoma and permanent recurrent laryngeal nerve injury did not occur in the NLND group, and their incidences were 0.5% and 0.3% in the PCLND group, respectively. PCLND had no significant correlation with LRR in patients with cN0 PTMC, and the absolute benefit for PTMC was small.